2002
DOI: 10.1098/rspb.2002.2192
|View full text |Cite
|
Sign up to set email alerts
|

Directional female preference for an exaggerated male trait in canary (Serinusanaria) song

Abstract: Motor constraints on vocal production impose a trade-off between trill rate and frequency bandwidth within birdsong. We tested whether domesticated canary (Serinus canaria) females, reared either in acoustic isolation or in aviary conditions, had a preference for broad bandwidth songs with artificially increased syllable rates. The copulation solicitation display (CSD) was used as an index of female preference. As predicted, both naive and experienced females were especially responsive to syllables with a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
169
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 48 publications
10
169
0
Order By: Relevance
“…Given these important roles of song, it is likely that vocal quality is subject to strong selective pressures (e.g., Marler and Slabbekoorn 2004). Singing birds may express quality by a variety of acoustic features of the vocal repertoire, among which are rapid temporal aspects such as trill and modulation rates (e.g., Podos 1997, Draganoiu et al 2002, Schmidt et al 2008, Suthers et al 2012. Production of high trill rates encompasses rapid switching between sound production and silent periods, and often includes rapid frequency modulation rates (e.g., Suthers and Goller 1997, Suthers and Zollinger 2008, Riede and Goller 2010, Elemans 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Given these important roles of song, it is likely that vocal quality is subject to strong selective pressures (e.g., Marler and Slabbekoorn 2004). Singing birds may express quality by a variety of acoustic features of the vocal repertoire, among which are rapid temporal aspects such as trill and modulation rates (e.g., Podos 1997, Draganoiu et al 2002, Schmidt et al 2008, Suthers et al 2012. Production of high trill rates encompasses rapid switching between sound production and silent periods, and often includes rapid frequency modulation rates (e.g., Suthers and Goller 1997, Suthers and Zollinger 2008, Riede and Goller 2010, Elemans 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory experiments, Vallet and colleagues (Vallet & Kreutzer 1995;Vallet et al 1998) found that phrases characterized by rapid repetition rates of frequency-modulated notes elicited the strongest female response in canaries. In later studies, Draganoiu et al (2002) found that, when given a choice, female canaries preferred trilled phrases that were beyond physical limitations in terms of the trade-off between trill rate and frequency bandwidth. Together these studies suggest that female preferences for trilled portions of songs in canaries might be driven by female preferences for portions of songs that are difficult to produce.…”
mentioning
confidence: 99%
“…This may also explain why canary females are specifically responsive to certain syllable types sung by males [44], and show preference for particular acoustic features of these syllables [66][67][68]. A preference for certain aspects of phonetics has also been found in other species: zebra finches [69], and Figure 2.…”
Section: Discussionmentioning
confidence: 95%